The academic environment: challenges in complying with security goals in pandemic times (Research, Society and Development, 2020)
Objective: In view of the scenario presented by Covid-19 and its challenges for the academic community, we carried out a literature review that theoretically supported the findings of our research-questionnaire on the challenges encountered by teachers in order to measure both the impact of the measures adopted by IES and the reaction of teachers to these challenges, such as social distance, preventive measures and distance learning. Methodology. We adopted for this study a mixed research or quali-quantitative research in which articles published in Portuguese were searched, between January 2020 and July 2020, on the database platforms BIREME, REDIB, LILACS, Virtual Health Library (VHL) , and Scientific Eletronic Library Online (SciELO) using the following descriptors: “Covid-19”, “academic challenges” and “security” in order to theoretically support the literature found with the answers offered by teachers in a questionnaire with closed and open questions. Discussion. With regard to the concerns of professionals in higher education, we proceeded with a questionnaire with questions to measure the level of information, prevention and protocols adopted by their respective HEIs with a view to preserving the health of their teaching, student, functional and thus preventing contagion. Results. The findings of the responses to the questionnaire pointed to the same concerns and urgencies discussed in the articles we found and we did the dialogue, the teacher's mental health during the pandemic.